European Union Enlargement and Equity Markets in Accession Countries - Podpiera, Richard (IMF Working Papers; Working Paper, 2005)
The announcement of the European Union enlargement coincided with a dramatic rise in stock prices in accession countries. This paper investigates the hypothesis that the rise in stock prices was a result of the repricing of systematic risk due to the integration of accession countries into the world market. We found that firm-level stock price changes are positively related to the difference between a firm's local and world market betas. This result is robust to controlling for changes in expected earnings, country effects, and other controls, although the magnitude of the effect is not very large. The differences between local and world betas explain nearly 22 percent of the stock price increase.